Stiffness-tuneable limb segment with flexible spine for malleable robots - Clark,AB; Rojas,N (IEEE, 2019)
Robotic arms built from stiffness-adjustable, con-tinuously bending segments serially connected with revolutejoints have the ability to change their mechanical architectureand workspace, thus allowing high flexibility and adaptation todifferent tasks with less than six degrees of freedom, a conceptthat we call malleable robots. Known stiffening mechanismsmay be used to implement suitable links for these novel roboticmanipulators; however, these solutions usually show a reducedperformance when bending due to structural deformation. Byincluding an inner support structure this deformation can beminimised, resulting in an increased stiffening performance.This paper presents a new multi-material spine-inspired flexiblestructure for providing support in stiffness-controllable layer-jamming-based robotic links of large diameter. The proposedspine mechanism is highly movable with type and range ofmotions that match those of a robotic link using solely layerjamming, whilst maintaining a hollow and light structure. Themechanics and design of the flexible spine are explored, anda prototype of a link utilising it is developed and comparedwith limb segments based on granular jamming and layerjamming without support structure. Results of experimentsverify the advantages of the proposed design, demonstratingthat it maintains a constant central diameter across bendingangles and presents an improvement of more than 203% ofresisting force at 180°.